The Evaluation of Inclusive Education Curriculum Program in PAUD Talenta Semarang - Lestari, Budi Dyah; Sutarto, Joko; Raharjo, Tri Joko (Universitas Negeri Semarang, 2019)
The purpose of this study was to analyze and to describe the inclusion curriculum held in (Early Childhood Education) PAUD Talenta Semarang, which included planning, organizing, implementing and evaluating. Inclusive education is an innovative and strategic educational approach to broadening access to education for all children with special needs. Inclusive education in PAUD Talenta Semarang is a PAUD service that provides opportunities for students who have abnormalities and have the potential for intelligence and/or special talents to attend education or learning in an educational environment together with students in general. Information about the implementation of inclusive PAUD was revealed through focused interview methods, observation, and documentation as data collection techniques. There were three procedures for qualitative data analysis in this study, namely data reduction, data presentation, and drawing a conclusion. The evaluation model used in this study was the CIPP model. The results of the study were: (1) The evaluation of Context, equitable access to education in PAUD Talenta was the fulfillment of the needs of parents and ABK; all ABK were able to be served, and the community has given full trust to the school in serving ABK. (2) The evaluation of Inputs, including elements of an assessment of school potential, program planning, budget, and human resources. (3) The evaluation of Process, school supervision which includes monitoring, supervising, evaluation, reporting, following-up to the results of supervision, was carried out by principals (who also plays a role as a psychologist and supervising supervisor) and educators. (4) The evaluation of Product of the implementation of inclusive education programs in PAUD Talenta Semarang seeks to assess the impact of the program implementation on student development.